Malignant Mesothelioma - Belli, Carmen; Anand, Santosh (IntechOpen, 2012)
This book brings together the knowledge of eminent experts in the field of malignant mesothelioma, a highly invasive tumor of mesothelium that is the protective lining covering several body cavities. Malignant mesothelioma shows extremely poor progression and is refractory to almost any kind of therapy putting considerable challenges in its treatment. This book covers many important aspects of malignant mesothelioma like epidemiology, immunology, molecular mechanisms and clinical options and will be useful to anybody interested in its history, pathology, and treatment.